A Smart Rural Project for Tourism of Madeira Island. Issue 8 (February 2019) - Rodrigues, Andreia; Virtudes, Ana
Abstract: Everywhere, there are cities, regions and countries which are struggling in order to reach a good position in terms of attractiveness, whether to catch more inhabitants or to get more visitants. All-over the world, cities like Bangkok in Thailand, Dubai in the United Arab Emirates or London in the United Kingdom, are witnessing, every year, a process of massive tourism. Many of these touristic places are very well-known as smart cities, because of their people, infrastructures, economy, governance, mobility, environment or simply their smart lifestyle. The rankings focused on the territories' performances are on the top of the agenda at the global scale. On the opposite side of the popularity coin, there are the small places, settled in rural areas, which are struggling to keep the few inhabitants who still remain there, and to attract visitors, as a way of boosting their social and economic dynamics. In this sense, this article is focused on the study of rural areas and tourism, to understand how small local communities in rural areas can use the smart cities knowledge and through tourism promote the economical local development. It will present a project solution for tourism purposes having as case study the tiny rural settlement of Fajã de Baixo, near to the Calheta in Madeira island, Portugal. The result shows that small rural settlements have an opportunity in touristic terms, using requirements of smart mobility and environmental solutions, promoting local identity, which is their main tourist attractiveness.